Association of Vitamin D and Diabetic Retinopathy in Patients with Type 2 Diabetes Mellitus - Parveen, Rizwana; Mishra, Pinki; Singh, Reema; Kapur, Prem; Agarwal, Nidhi B. (Annals of the National Academy of Medical Sciences (India), 2017)
Objective: To assess the association of vitamin D (VD) and diabetic retinopathy (DR) in patients with type 2 diabetes mellitus (T2DM). Method: Literature search was conducted for studies assessing the association of VD and DR. Total 9 studies have a sum total of 1741 patients were included for ﬁnal analysis. Results: The concentration of VD in controls ranged from 17.5±3.6 to 31.9±12.9 ng/ml, while for T2DM patients without retinopathy it ranged from 11.94±4.21 to 23.10±6.12 ng/ml. T2DM patients with retinopathy had the lowest concentration, ranging from 10.02±5.61 to 19.25±7.86 ng/ml. Ahigher percentage of T2DM patients without (50.7% to 68.80%) and with (31.2% to 79.63%) retinopathy had VD deﬁciency (VDD). Discussion: An inverse association between VD levels and DR was observed. The concentration of VD decreases as the stage of DR advances. VD seems to be an easily modiﬁable risk factor for DR. Thus, VD supplementation should be encouraged in population at higher risk for diabetic complications.
Keywords: Vitamin D; cholecalciferol; retinopathy; vitamin D deﬁciency; diabetic retinopathy; diabetic complications; type 2 diabetes; systematic review